Penyuluhan dan Kampanye Nilai-Nilai Multikulturalisme di Tengah Badai Covid-19 - Murniati Agustian; Aldearni Yuana; Chatarina Siti Rosy Yanti; Oktavia Leni Ajeng (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
The impact of the new identities of Covid-19 such as confirmed as positively infected, conducted self-isolation, stimulate intolerant attitudes in society. The public's attitudes towards the Covid-19 cases are very substantially contrary to the values in a multicultural society. The panic buying of medical equipment, medicines and vitamins, refusing the Covid-19 burial protocols even for medical personnel. This activity is an integration of multicultural education courses with community service. The purpose of this activity is to promote a campaign for individual identity, empathy, critical thinking, equal interaction, cooperative interaction, openness, and different status elimination. Videos are given directly to the community and through social media as the campaign process. In preparation and implementation, lecturers are assisted by students to create innovative media related to the current situation. There are 10 groups that produce media, in the form of animated videos. Before the media is used, there is a product evaluation by lecturers and classmates. After the revision, the media is used to conduct a multicultural campaign in the society. As a result of this activity, more than 1000 people who were exposed to the campaign, almost all considered it positive because the messages conveyed were delivered to the community.